Self Assessment of Dental students' Perception of Learning Environment in Croatia, India and Nepal - Manu Batra; Ana Ivanišević Malčić; Aasim Farooq Shah; Reshu Agrawal Sagtani; Ivana Medvedec Mikić; Petra Tariba Knežević; Silvana Jukić Krmek; Davor Illeš (University of Zagreb. School of Dental Medicine, 2018)
Aim: The aim of this study was to assess dental students' perception of different learning environment in India, Nepal and Croatia. Methods: The study was conducted during a period of academic year 2016/17. A total of 849 dental students participated in the study. There were 188 respondents from Croatia, 373 from India, and 288 from Nepal. Non-responders were not followed up. The Dental Student Learning Environment Survey (DSLES) was used which consisted of 55 items subdivided into seven scales. The scales measured the following perceptions: Flexibility, 'Student-to-Student Interactions, Emotional Climate, Supportiveness, Meaningful Experience, Organization and Breadth of Interest. Statistical analysis of the data utilised the Kolmogorov Smirnov test. The Kruskal-Wallis "non-parametric ANOVA" was also used to test the differences between the countries. A post hoc analysis was performed using Ranks tables and the Median test. Results: The response rate was 26.9%. Significant differences between the countries were found for all DSLES variables (Kruskal-Wallis, p<0.01). The Median test also showed significant differences between the countries for all DSLES variables (p<0.01). The scales with the highest mean values were 'Student-to-student interactions' in India and Nepal, and the 'Emotional Climate' in Croatia. Conclusions: Students in Croatia rated their school only with grades excellent and good, while their colleagues in India and Nepal were more critical. Despite the different settings in three countries, 'Flexibility' was identified as the area of weakness in all three educational systems.